2022
DOI: 10.1002/dvdy.474
|View full text |Cite
|
Sign up to set email alerts
|

Distinct regulatory states control the elongation of individual skeletal rods in the sea urchin embryo

Abstract: Background: Understanding how gene regulatory networks (GRNs) control developmental progression is a key to the mechanistic understanding of morphogenesis. The sea urchin larval skeletogenesis provides an excellent platform to tackle this question. In the early stages of sea urchin skeletogenesis, skeletogenic genes are uniformly expressed in the skeletogenic lineage. Yet, during skeletal elongation, skeletogenic genes are expressed in distinct spatial sub-domains. The regulation of differential gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 73 publications
1
23
0
Order By: Relevance
“…Microinjections were conducted similarly to [44]. The eggs were injected with an injection solution containing 0.12M KCl, 0.5µg/µl Rhodamine Dextran and 900µM of MASOs.…”
Section: Rock Masos Injectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microinjections were conducted similarly to [44]. The eggs were injected with an injection solution containing 0.12M KCl, 0.5µg/µl Rhodamine Dextran and 900µM of MASOs.…”
Section: Rock Masos Injectionsmentioning
confidence: 99%
“…QPCR was carried out as described in [44]. Complete list of primer sequences used for the experiments in provided there.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…tunicates and vertebrates) (Figure 1 A). Echinoderms, which include sea urchins and sea stars, are part of the sister group to chordates and as such occupy a critical phylogenetic position to understand evolution of vertebrate organs, while offering a series of experimental advantages (Annunziata et al, 2019; Annunziata et al, 2013; Annunziata et al, 2014; Arnone et al, 2016; Ben-Tabou de-Leon, 2022; Cary et al, 2019; Cary & Hinman, 2017; Cheatle Jarvela & Hinman, 2014; Hinman & Cheatle Jarvela, 2014; Meyer & Hinman, 2022; Morgulis et al, 2019; Morgulis et al, 2021; Tarsis et al, 2022; Wolff & Hinman, 2021). Here, we use the sea star Patiria miniata as a powerful system to study tubulogenesis within an intact organism.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with axitinib, a selective VEGF receptor inhibitor, revealed that VEGF signaling is required for early ingression and also PMC migration and patterning during later stages of development (Adomako-Ankomah and Ettensohn, 2013; Morgulis et al, 2019; Morgulis et al, 2021). Genes with localized expression at the tips of the growing arms are also downregulated in axitinib-treated embryos (Morgulis et al, 2019; Sun and Ettensohn, 2014; Tarsis et al, 2022).…”
Section: Introductionmentioning
confidence: 99%